On a bioenergetic four-compartment model for human exercise - Sundström, D. (Sports Engineering, 2016)
Bioenergetic models for exercise performance simulations and pacing strategy optimizations currently lag behind empirical knowledge in human bioenergetics. Therefore, the objective of this study was the construction of a four-compartment hydraulic bioenergetic model that incorporates separate oxidative phosphorylation of lipids and carbohydrates and describes the regulation of these energy substrates` utilization. Furthermore, the aim was also to model efficiency and the impact of muscle fatigue and the force-velocity relationship on the maximal attainable rate of energy expenditure. The model is formulated with five systems of differential equations that regulates the fluid levels in three of the compartments, while the fat compartment energy is kept constant. Regulations had to be imposed on the system of compartments to achieve the desired carbohydrate dependent functionality and efficiency of the model. Equilibrium equations are modeled for the alactic compound composition and a constraint is modeled for the maximal energy expenditure rate, dependent on the intramuscular inorganic phosphate. A separate force-velocity relationship is modeled to constrain power output at low speeds and efficiency is modeled with a linear but off-set relationship between power output and rate of energy expenditure. The relative aerobic contribution to total energy expenditure showed good congruence with empirical results, while time to exhaustion was overestimated due to the constraint on maximal rate of energy expenditure. Therefore, further experimental studies are necessary for complete validation of the model.